The Future Of Sharia Based Village Business Agencies Religious Response Management Of Village-Owned Enterprises In Central Lombok - Suhirman Suhirman (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
AbstractPurpose - This study aims to uncover and explain the opportunities and future of Village-Owned Enterprises (BUMDes) in Central Lombok managed by the Islamic financial system which is viewed from the perspective of the manager's religious response.Method - This research is a qualitative-descriptive research. Data collection methods using questionnaires and unstructured interviews. The data used in this study are primary data and analyzed qualitatively. The population of this study is the managers of BUMDes in Central Lombok with a sample of 52 people.Result - This research shows that based on organizational affiliation and Islamic character as well as Islamic commitment of managers, BUMDes in Central Lombok is very likely to be managed syariah. Whereas in terms of the manager's response to the sharia bank system and its products, the BUMDes argumentation that is not managed in a sharia way shows the opposite opportunity.Implication - Activists, practitioners, and Islamic economic stake holders need to provide education and dissemination to BUMDes managers and stakeholders about the advantages and strengths of sharia-based financial management, both in terms of religiosity and profitability.Originality- This study focuses on revealing the opportunities and future of Sharia-based BUMDes management from the perspective of the religious response of BUMDes managers in Central Lombok.